EFFECTIVENESS OF THE NATIONAL NARCOTICS AGENCY OF BALANGAN REGENCY IN PREVENTING AND ERADICATING NARCOTICS AMONG ADOLESCENTS IN BALANGAN REGENCY - Haji Mukti Ramadhani; M. Husaini; Lily Misliani (International Journal of Economic Integration and Regional Competitiveness, 2024)
Objective: This study aimed to determine the effectiveness of the National Narcotics Agency (BNN) in preventing and eradicating narcotics abuse among adolescents in Balangan Regency, and to explore the factors influencing its performance. Method: The research employed a qualitative approach with a descriptive-qualitative design. Data collection techniques included interviews, observations, and documentation, using snowball sampling with 12 participants. The collected data were analyzed through data reduction, presentation, and conclusion drawing, ensuring credibility through extended observations, triangulation, and member checks. Results: The study found that the effectiveness of the BNN's performance in preventing and eradicating narcotics among adolescents in Balangan Regency was fairly effective. Planning and implementation indicators were effective, but monitoring and target achievement indicators were not. Factors influencing effectiveness included inhibiting factors such as the lack of field officers and insufficient achievement of targets. Supporting factors included good activity standards, prevention efforts, and rehabilitation processes. Novelty: The novelty of this study lies in its focus on the effectiveness of the BNN's performance in the context of a local district, highlighting the challenges in monitoring, target achievement, and the lack of field officers. The study provides valuable insights into the structural and operational constraints faced by the BNN in implementing narcotics prevention programs, contributing to the understanding of local-level narcotics control.